Tourist Loyalty Antecedents On Halal Tourism In Yogyakarta - Helmi Maulana Hendrawan; Istyakara Muslichah (LPPM ISNJ Bengkalis, 2023)
Halal tourism is being developed to enhance Islamic law-based destinations' social, cultural, and destination values. However, the determinants influencing the antecedents of tourist loyalty to halal tourism have yet to be studied extensively. This study aims to analyze the role of antecedents of traveller loyalty in halal tourism in Yogyakarta. SEM-based quantitative research was used for its analysis. The study involved 200 participants, with the main criteria being that they had visited tourist destinations in Yogyakarta. The participants were selected by purposive sampling and then given an online questionnaire containing statements according to the research variables. All data were analyzed with SEM-AMOS. The findings show that the halal tourism experience, value perception, and satisfaction influence traveller loyalty. In contrast, traveller satisfaction is influenced by the halal tourism experience and value perception. Hence, the better the management of halal tourism in Yogyakarta, the more it contributes to increasing traveller satisfaction, which has implications for traveller loyalty. This research provides perspectives and technical and theoretical implications for entrepreneurs, governments, and managers of halal tourism destinations to increase socialization activities and intensify the concept of halal tourism, which has been proven to have a positive and significant effect on satisfaction and loyalty.